Long-term changes in chemical components in the meadow pipit (Anthus pratensis) in the formerly heavily polluted Eastern Sudetes Mountains - Bureš, Stanislav; Hekera, Petr; Jašková, Paulína (Environmental science and pollution research international, 2025)
The Eastern Sudetes Mountains (Northern Moravia, Czech Republic) were among the most polluted regions of Europe due to toxic metal depositions and acid rain, until the desulfurization of emissions from coal power stations and reduction of heavy industry which took place in the 1990s. This study provides a comparison of data on the levels of calcium, lead, cadmium, and aluminum in soil, meadow pipit (Anthus pratensis) nestlings, and their available diet in 1994-1999 and in 2017-2019. The soil pH and exchangeable amount of calcium and lead increased slightly. The concentration of calcium in potential prey (invertebrates) increased slightly, and lead and cadmium levels decreased. The amount of calcium and lead in nestling bodies decreased in 2017-2019, while cadmium and aluminum levels remained unchanged after accounting for nestling age. The age of nestlings had an effect on aluminum only, when its content decreased with age. The principal component analysis revealed close association between calcium and lead. The consequences of recent leaching of basic cations, mainly calcium, and increasing bioavailability of lead in soils for future reproduction of the meadow pipit are discussed.
Keywords: kadmium; vápník; Cadmium; Upland; Česká republika; Passerines; Soil Pollutants; hliník; Calcium; olovo; Animals; Aluminum; Czech Republic; zvířata; Soil chemistry; Invertebrates; látky znečišťující půdu; půda; Environmental Monitoring; Lead; Recovery; Soil; monitorování životního prostředí